Finite Element Analysis of Generalized Ligament Laxity on the Deterioration of Hallux Valgus Deformity (Bunion) - Wong, Duo Wai-Chi; Wang, Yan; Chen, Tony Lin-Wei; Yan, Fei; Peng, Yinghu; Tan, Qitao; Ni, Ming; Leung, Aaron Kam-Lun; Zhang, Ming (Frontiers in Bioengineering and Biotechnology, 2020)
Hallux valgus is a common foot problem affecting nearly one in every four adults. Generalized ligament laxity was proposed as the intrinsic cause or risk factor towards the development of the deformity which was difficult to be investigated by cohort clinical trials. Herein, we aimed to evaluate the isolated influence of generalized ligament laxity on the deterioration using computer simulation (finite element analysis). We reconstructed a computational foot model from a mild hallux valgus participant and conducted a gait analysis to drive the simulation of walking. Through parametric analysis, the stiffness of the ligaments was impoverished at different degrees to resemble different levels of generalized ligament laxity. Our simulation study reported that generalized ligament laxity deteriorated hallux valgus by impairing the load-bearing capacity of the first metatarsal, inducing higher deforming force, moment and malalignment at the first metatarsophalangeal joint. Besides, the deforming moment formed a deteriorating vicious cycle between hallux valgus and forefoot abduction and may result in secondary foot problems, such as flatfoot. However, the metatarsocuneiform joint did not show a worsening trend possibly due to the overriding forefoot abduction. Controlling the deforming load shall be prioritized over the correction of angles to mitigate deterioration or recurrence after surgery.